EFFORTS TO DEVELOP TEACHERS BECOME A HEALTH CADRES WHO HAS KNOWLEDGE OF THE BENEFITS OF VITAMIN D FOR THE BODY IMMUNITY SYSTEM - Debby Mirani Lubis Lubis; Meizly Andina (University of Muhammadiyah Sumatera Utara, 2019)
One of the efforts in improving public health is by promoting health promotion in the school environment and forming health cadres that can be utilized within the school environment (UKS) and the community. Vitamin D is one of the vitamins needed by the body. Vitamin D has only been known to ordinary people to have benefits in bone health. But not many people know that vitamin D is also beneficial for endurance, namely vitamin D can fight bacteria / germs that enter the body so as to prevent a person from experiencing disease. Therefore, the purpose of this service is to provide and provide information to Muhammadiyah elementary school teachers so that they have knowledge about the benefits of vitamin D for endurance. The method of approach taken is through a participatory approach (participatory approach). The Proposing Team and partners together develop a plan of activities, methods, goals, objectives and targets that must be achieved. This activity began with the development of Muhammadiyah youth as school health cadres. The training activities were carried out in the form of health seminars for elementary school Muhammadiyah teachers. Keywords: Vitamin D, Primary teacher, Muhammadiyah